Conceptual Representation of Culture in EFL Textbook Images: A Multimodal Analysis - Suwandani, Febi; Hidayati, Sari (Dinamika Ilmu, 2025)
This study investigated the types of culture presented in EFL school textbooks in Indonesia. Qualitative content analysis and the Kress & van Leeuwen’s conceptual representation framework were employed to analyze the data in two textbooks widely used at the Junior high school level. The findings show that both textbooks portray a rather disproportionate representation of culture. Target culture is represented more dominantly in the global textbook, while the locally produced textbook emphasizes the presentation of source culture. This finding suggests that the former textbook, despite some localization, is intended to appeal to a wider global audience, while the latter implies an attempt to preserve local identity and localize the context of English language learning. Such imbalanced representation has the potential to impede students’ acquisition of intercultural communicative competence. Therefore, there is an urgency for material developers to provide students with balanced cultural content, as well as an active role from the teacher to appropriately select learning materials to supplement the drawbacks of the textbooks.